2013
DOI: 10.4103/1463-1741.110289
|View full text |Cite
|
Sign up to set email alerts
|

The use of fractal tones in tinnitus patient management

Abstract: A variety of noises have been employed for decades in an effort to facilitate habituation, mask, or suppress tinnitus. Many of these sounds have reportedly provided benefit, but success has not been universal. More recently, musical stimuli have been added as a sound therapy component. The potential advantages of using such stimuli, in particular fractal tones, in combination with amplification are discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…It may be preferable for some people but not for others. The use of amplification, combined with flexible music-like signals containing relaxation inducing properties may be a further asset to tinnitus management procedures [2]. An example is the use of fractal (randomly generated) tones, which differs from conventional music in terms of its familiarity but similar preferences for using music for relaxation and tinnitus sound therapy appear to apply.…”
Section: In-ear Medical Devices As Instrument For Current Acoustic Thmentioning
confidence: 99%
“…It may be preferable for some people but not for others. The use of amplification, combined with flexible music-like signals containing relaxation inducing properties may be a further asset to tinnitus management procedures [2]. An example is the use of fractal (randomly generated) tones, which differs from conventional music in terms of its familiarity but similar preferences for using music for relaxation and tinnitus sound therapy appear to apply.…”
Section: In-ear Medical Devices As Instrument For Current Acoustic Thmentioning
confidence: 99%
“…Examples of these features include sound signals that are intended to be conducive to relaxation [39]; alternatively, others can be applied in order to provide some form of sound enrichment or masking. A low number of small-scale studies have reported that these systems can be useful for the management of tinnitus, with the supplementation of appropriate counseling [33].…”
Section: Discussionmentioning
confidence: 99%
“…Sweetow from San Francisco criticizes sound therapy and the missing evidence of many studies [145] because they generally do not consider sufficiently the concomitant hearing loss. He presents new music-related therapy approaches in terms of interrupted sounds.…”
Section: Neuromodulation – Instrument-based Medical Interventionsmentioning
confidence: 99%